Harrison White and the Practice of Sociology - Peter Bearman; Ronald L. Breiger (Sociologica)
We introduce the topics and foci of the six articles in this special issue devoted to the work of Harrison White, who passed away in May 2024. We asked each author to reveal some aspects of White’s craft, while recounting how their own work has in some respects been entangled with the research problems and vision that he has articulated. Each essay is at once scholarly, innovative, and deeply personal.